Rare case of dilated cardiomyopathy in case of severe vitamin D deficiency - D, Karthik; Richa, Richa; Raval, Nidhish; Pande, Vineeta; Jadhav, Renuka; Mane, Shailaja (Journal of Neonatal Surgery, 2025)
Dilated cardiomyopathy (DCM) in infants is a rare but potentially reversible condition when caused by hypocalcemia, most often secondary to vitamin D deficiency. This case report presents a 40-day-old exclusively breastfed female infant who developed non resolving cough and was found to have DCM with significantly decreased left ventricular function. Biochemical investigations revealed low levels of vitamin D and calcium, while parathyroid hormone (PTH) levels remained normal. A similar vitamin D deficiency was identified in the mother. Upon administration of calcium and vitamin D supplementation, the infant’s cardiac function improved markedly within a week, with full recovery confirmed by echocardiography at three months. This case underscores the importance of early recognition and treatment of hypocalcemia-induced cardiomyopathy, especially in infants born to vitamin D-deficient mothers. Proactive maternal and infant vitamin D supplementation could prevent such life-threatening manifestations.